International trade outlook for Latin America and the Caribbean (UN ECLAC SantiagoCL, 2017)
Describes the current international context and the recovery of trade in the region. Reviews the region's performance in global trade in services in general and in modern services in particular. Provides an overview of Latin America and the Caribbean's share of the world agricultural trade since 2000 and offers some policy recommendations for increasing the sector's contribution to regional development.
Documentation Centre has: 2017- 20